Społeczna produktywność szkół wyższych, czyli czego oczekuje się obecnie od uniwersytetów? = Social productivity of universities. What are universities expected to do nowadays? - Jelonek, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the concept of social productivity of universities elaborated within the preparation of PhD thesis entitled "Social productivity of universities - new concept of teaching productivity". The process of constructing social productivity model was based on the reconstruction of theoretical concept present in the consciousness of social representatives and universities.
Keywords: szkolnictwo wyższe; oczekiwania